Mr PENGARUH HARGA DAN PROMOSI TERHADAP KEPUASAN PELANGGAN STARBUCKS PEKANBARU: The Influence of Price and Promotion on Customer Satisfaction at Starbucks Pekanbaru - Chandra Chandrio; Nila Rifai (Bogor Hospitality Journal, 2026)
This study aims to analyze the influence of price and promotion on customer satisfaction at Starbucks in Palangka Raya. The research employed a quantitative method with a multiple linear regression approach. Data were collected through questionnaires distributed to 200 respondents who are Starbucks customers. The results show that both price and promotion variables have a positive and significant effect on customer satisfaction. The price variable has a significance value of 0.003 with an influence level of 0.303, indicating that appropriate pricing can enhance satisfaction with the services provided. Meanwhile, the promotion variable has a significance value of 0.000 with an influence level of 0.411, suggesting that effective promotions can strengthen positive perceptions and improve customer experience. These findings align with previous studies emphasizing the importance of competitive pricing and innovative promotions. Therefore, companies need to design targeted marketing strategies, adjust prices to consumer purchasing power, and implement sustainable promotional innovations.